Pemanfaatan Smartphone sebagai Media Pembelajaran Mandiri pada Anak di Kabupaten Kupang - Wildaya Senge (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Kupang, 2023)
The purpose of this study was to determine and to describe the use of smartphones as an independent learning media fo High School Students in Manusak Village, Kupang Regency. The informants of this study consisted of students who used smartphones as a media for independent learning. Research data were collected through observation, interviews, and documentation. The research data were analyzed using qualitative analysis techniques moving in a circle, namely data reduction, data display, and drawing conlusions. The study indicated that the benefits of smartphone as learning media for students were to increase students’ knowledge, as a source of entertainment for students who feel bored while studying. Besides, its impact on students were it can divert students’ thoughts and attention, lack of social interaction between students, student cheating oftem occurs in learning (copy and paste from internet).